The role of infection in morphea disease - Fatemeh Farhangdoost (Reviews in Clinical Medicine, 2015)
Morphea is a skin disorder that leads to the sclerosis of the dermis and subcutaneous tissue. In epidemiologic studies, the incidence rate of approximately 0.4 to 2.7 per 100,000 people has been reported that is equal in adults and children. Based on clinical findings of disease and presentations, morphea disease has been divided into four major types including plaque-type, linear, generalized and a miscellaneous group with morphologically distinct phenotypes. Overall, plaque-type is the most common type of morphea. This disease is characterized by three main histopathologic features that include deposition of collagen in the dermis sometimes with extension to subcutis, vascular changes and an inflammatory cell infiltration, particularly in early lesions. Morphea is a multifactorial process that its main underlying cause is not completely known but the most common causes related to the genesis of morphea including trauma, radiation, medications, infection, autoimmunity and microchimerism. In this paper, we review the literature about the role of infection in the genesis of morphea.